2022
DOI: 10.3390/s22082966
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer Defect Detection in Intra-Ply Hybrid Composite Material (GF/CF) Using a Capacitance-Based Sensor

Abstract: Combining two types of reinforcement fiber in a common matrix may lead to different failure modes such as micro-cracks between the layers when the structure is subjected to lower stress levels. Real-time damage detection should be integrated into the hybrid composite structure to provide structural integrity and mitigate this problem. This paper outlines the working mechanisms and the fabrication of an integrated capacitive sensor in an intra-ply hybrid composite (2 × 2 twill weave). Uniaxial tensile and flexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This suggests that the coated yarn did not cause early-stage damage to the glass fiber-reinforced polymer, unlike previous research where carbon fiber yarn was used as an electrode and integrated into glass fiber composites. This indicates that the current approach is less detrimental to the composite’s integrity [ 29 ]. The gauge factor, computed using a linear least squares method over a 0.8% strain range for the embedded capacitive sensors according to Equation (1), was approximately 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the coated yarn did not cause early-stage damage to the glass fiber-reinforced polymer, unlike previous research where carbon fiber yarn was used as an electrode and integrated into glass fiber composites. This indicates that the current approach is less detrimental to the composite’s integrity [ 29 ]. The gauge factor, computed using a linear least squares method over a 0.8% strain range for the embedded capacitive sensors according to Equation (1), was approximately 1.…”
Section: Resultsmentioning
confidence: 99%
“…Their findings indicated that damage occurred at an early stage of axial stress. In a study by Alblalaihid et al [ 29 , 30 ], a smart intra-ply hybrid composite material (comprising glass fiber and carbon fiber) based on capacitance was developed. It was observed that failure occurred at a low level of axial stress due to the combination of low-elongation and high-elongation fibers within a common matrix.…”
Section: Introductionmentioning
confidence: 99%
“…To manufacture a sample of Kevlar-carbon hybrid composites which consisted of seven layers as shown in Figure 1b, the hand layup process was used. More detail of the process of integrating and manufacturing the smart material can be found in [2]. To characterize the smart material, a tensile test was conducted as shown in Figure 1c.…”
Section: Methodsmentioning
confidence: 99%
“…FEA methods have been broadly utilized as numerical tools for analyzing and anticipating the mechanical properties and performance of engineering materials involving CFRPCs. There are many sectors that benefit from composite material simulation, such as the aerospace, aeronautics, energy, automotive, civil, sports, and even electronics sectors [59,[62][63][64][65][66]. This is because FEA is a great method to prove designs before an objective prototype of the CFRPC is fabricated.…”
Section: Finite Element Modeling Of Recycled Cfrpcsmentioning
confidence: 99%
“…This is because FEA is a great method to prove designs before an objective prototype of the CFRPC is fabricated. Nevertheless, it is possible to understand and anticipate many phenomena, including damage and the CF and matrix interface, when the CFRPC is exposed to severe conditions, such as dynamic loading, high temperatures, and high pressures, when using the FEA approach [59,62,63].…”
Section: Finite Element Modeling Of Recycled Cfrpcsmentioning
confidence: 99%